Development of a Sharia Financing Model to Increase MSME Revenues in Lubuk Pakam District - Julita Julita (AIBPM Publisher, 2021)
This study aims to find out how the relationship or influence of Islamic financing consisting of mudharabah, musyarakah, murabahah, and ijarah to increase the income of MSMEs in Lubuk Pakam District. By using Smart PLS version 23 data analysis. (Suci, 2017). MSMEs have been proven to have a very important role, this can be seen when MSMEs were able to save the Indonesian economy during the 1997 monetary crisis. At that time MSMEs were able to provide job opportunities in times of crisis and played a major role in efforts to increase people's income. The relationship between sharia financing and MSME income is that financing has an influence on increasing the income of micro business actors. This increase in income was due to additional venture capital in developing the business. Simultaneously, it can be concluded that Mudharabah, Musyarakah, Murabahah, and Ijarah have a positive effect on the income of MSMEs in Lubuk Pakam District.